Proteinuria as a Biomarker for COVID-19 Severity - Ouahmi, Hajar; Courjon, Johan; Morand, Lucas; François, Juliette; Bruckert, Vincent; Lombardi, Romain; Esnault, Vincent; Seitz-Polski, Barbara; Demonchy, Elisa; Dellamonica, Jean; Boyer-Suavet, Sonia (Frontiers in Physiology, 2021)
Background Renal involvement in syndrome coronavirus 2 (SARS-CoV-2) infection has been retrospectively described, especially acute kidney injury (AKI). However, quantitative proteinuria assessment and its implication in coronavirus disease 2019 (COVID-19) remain unknown. Methods In this prospective, multicenter study in France, we collected clinical and biological data including urinary protein to creatine ratio (UPCR) in patients presenting with moderate to severe COVID-19. Clinical outcome was analyzed according to the level of UPCR. Results 42/45 patients (93.3%) had renal involvement (abnormal urinary sediment and/or AKI). Significant proteinuria occurred in 60% of patients. Urine protein electrophoresis showed tubular protein excretion in 83.8% of patients with proteinuria. Inflammatory parametersand D-dimer concentrations correlated with proteinuria level. Patients who required intensive care unit (ICU) admission had higher proteinuria (p = 0.008). On multivariate analysis, proteinuria greater than 0.3 g/g was related to a higher prevalence of ICU admission [OR = 4.72, IC95 (1.16–23.21), p = 0.03], acute respiratory distress syndrome (ARDS) [OR = 6.89, IC95 (1.41–53.01, p = 0.02)], nosocomial infections [OR = 3.75, IC95 (1.11–13.55), p = 0.03], longer inpatient hospital stay (p = 0.003). Conclusion Renal involvement is common in moderate to severe SARS-CoV-2 infection. Proteinuria at baseline is an independent risk factor for increased hospitalization duration and ICU admission in patients with COVID-19.